Die lewe en werk van Frances Young (1939–) en Dorothee Sölle (1929–2003): ŉ Leksikografiese bydrae tot Reformasie 500 - Van Wyk, Tanya ca. 20./21. Jh. (HTS teologiese studies, 2017)
The contribution of two women to the Reformed heritage: The life and work of Frances Young (1939–) and Dorothee Sölle (1929–2003). This article is a lexicographical overview of the life and work of two specific women, Frances Young and Dorothee Sölle. The purpose of this is to highlight the reformed character of their respective theologies. Both are characterised by reflection on and reaction to the fragility of human life and the brokenness of the human condition. They are among the ‘cloud of witnesses’ that bear testimony to the impact and heritage of the Reformation.